Persistent ciprofloxacin exposure induced the transformation of Klebsiella pneumoniae small colony variant into mucous phenotype - Zou, Hua; Li, Qian; Su, Yan; Zhang, Lei; Zhang, Xinyuan; Li, Chunli (Frontiers in Cellular and Infection Microbiology, 2023)
Small colony variant (SCV) is a bacterial phenotype closely related to persistent and recurrent infections. SCVs are mutations that occur within bacterial populations, resulting in a change in bacterial morphology and the formation of small colonies. This morphological change may enhance bacterial resistance to antibiotics and contribute to persistent and recurrent infections. We isolated Klebsiella pneumoniae (KPN) and its SCV from a child with recurrent respiratory tract infections. After treating KPN and SCV with subinhibitory concentrations of antibiotics, we found that ciprofloxacin induced the SCV transition to the mucoid phenotype. We found that the growth of mucoid Klebsiella pneumoniae was significantly slower than maternal strain and SCV though growth curves. Serum resistance experiments showed that mucoid strains had significantly higher serum resistance compared to maternal strain and SCV. Macrophage phagocytosis experiments revealed that SCV had significantly higher intracellular survival rates compared to maternal strain and mucoid strains. Differential gene analysis of three strains revealed that the mucoid strain contained DNA polymerase V subunit UmuC gene on the plasmid, while the SCV strain had an additional IcmK family IV secretion protein on its plasmid. Our study showed the SCV of KPN changed to a mucoid colony when exposed to subinhibitory concentrations of ciprofloxacin. The higher resistance of serum of mucoid colonies was possibly related to the UmuC gene, while the increased intracellular survival of SCV may be related to the IcmK family type IV secretion proteins.